2007
DOI: 10.1111/j.1095-8649.2007.01471.x
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and seasonal behaviour of adult and juvenile European catfish as determined by radio‐telemetry in the River Berounka, Czech Republic

Abstract: The first telemetry study analysing behaviour of the largest freshwater predator in European rivers, Silurus glanis, was performed bimonthly during the years 2002-2004. Movement of juveniles and adults occurred mostly in the same time intervals. The only statistical differences occurred for nocturnal activity in spring and autumn. In spring and winter, activity was low with the peaks during daylight, and in autumn, maximal movement was recorded during dusk. In summer, the European catfish were active across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 38 publications
(42 reference statements)
7
71
2
Order By: Relevance
“…Among these 12 hooked fish, the angler caught 6. These results also confirm that European catfish is not only a nocturnal predator but can be also active across diurnal periods in rivers, see also [18]. Individual body size significantly differed between behaviour types (Kruskal-Wallis test, p < 0.01) with hooked individuals larger than individuals exhibiting Ignore behaviour (Mann-Whitney test, p < 0.01), Approach behaviour (p < 0.01), Taste behaviour (p < 0.01) and Spit behaviour (p < 0.01) (Fig.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Among these 12 hooked fish, the angler caught 6. These results also confirm that European catfish is not only a nocturnal predator but can be also active across diurnal periods in rivers, see also [18]. Individual body size significantly differed between behaviour types (Kruskal-Wallis test, p < 0.01) with hooked individuals larger than individuals exhibiting Ignore behaviour (Mann-Whitney test, p < 0.01), Approach behaviour (p < 0.01), Taste behaviour (p < 0.01) and Spit behaviour (p < 0.01) (Fig.…”
Section: Resultssupporting
confidence: 75%
“…We documented the feeding motivation of European catfish toward a live baited hook, by exposing the same type of bait in similar natural environmental conditions to catfish individuals and describing their behaviour toward the bait once they located the prey. Diel dualism in the activity of European catfish occurs in the wild and diel activity and energy consumption differs across the seasons [18]. In a Czech river, European catfish were active across the whole 24 h in summer [18].…”
Section: Discussionmentioning
confidence: 99%
“…In cold water during winter time, the activity of European catfish is minimal (Slavík et al, 2007;Copp et al, 2009). However, our telemetry study revealed the possibility of short-term high activity in winter in response to sub-optimal and/or potentially lethal environmental variables.…”
Section: Discussionmentioning
confidence: 78%
“…In our case, the tracked individuals displayed site fidelity at first. Each individual had its stable resting place, and the HR was minimal, which could have been bolstered by the low temperature (Slavík et al, 2007). Later on, a large aggregation of fish in two restricted areas took place.…”
Section: Id -Identification Number Of Individualmentioning
confidence: 99%
See 1 more Smart Citation